Chilled water storages an alternative solution to the problem of brownouts in the Philippines - Santos, Arturo Martin B.
The problem of brownouts in the Philippines, specifically in Luzon, has been largely due to the high value of the peak power demand which our local utilities have difficulty supplying. This paper discusses the merits to both the consumers and the electric utilities of installing chilled water storages in addition to the benefit of reducing the possibilities of having power outages that these systems may potentially bring. Written in a form that is readable by persons with varied backgrounds in engineering or allied fields.